Creativity as a Dimension in School Motivation - Sichi Ojanama, Amparo Isabel (2024)
The focus of this research is the field related to creativity contextualized in the school environment. Among the aspects of the key role that creativity could play, it has been proposed to explore its link with motivation in terms of its implication in learning. A systematic review of the literature was carried out on the categories creativity-creative thinking and motivation in the year 2023 with articles published in research publication bases. Research was sought that would allow us to analyze the aforementioned categories, as well as the relationships between both in the context of primary education. Specifically, some of the bases of experience and motivation were examined. As a result, it is concluded that the development of both categories involves the mobilization of cognitive, affective and active processes and that the relationship between them is mutually productive for the success of the learning of basic education students as long as those responsible assume them from a pedagogical and didactic perspective.